Low-temperature direct electrochemical splitting of H2S - Velazquez-Rizo, Martin; Cavazos Sepulveda, Adrian Cesar (Frontiers in Chemical Engineering, 2023)
Hydrogen is considered as one of the most promising decarbonized fuel. However, its applicability is limited due to the ecological constraints of its production. Hydrogen sulfide (H2S) is widely available in oil and natural gas reservoirs and has the possibility of becoming an energetically favorable source of hydrogen. Nevertheless, its electrochemical separation into H2 and elemental sulfur has not been successfully achieved at industrial scale, mainly because of the sulfur poisoning of the electrodes at the sulfur oxidation half-reaction. This review highlights the progress of the direct electrolytic separation of H2S below the sulfur dew point, where the sulfur poisoning effect becomes more prominent. The article discusses the different technologies and approaches explored to improve the energy efficiency and stability of H2S electrolytic systems, including the recent use of nanostructured electrodes and novel sulfur solvents as electrolytes.